Selected aspects of research on advanced states deformation of thin-wall aircraft composite structures - Lis, Tomasz (Technical Sciences, 2025)
The paper concerns the most significant and characteristic stages of manufacturing and testing the properties of aircraft thin-wall composite structures. Structures of this kind, due to the high requirements in terms of safety, durability and economy of aircraft operation, force the emergence of a number of often mutually contradictory design assumptions. The basic problem is to ensure the necessary strength and stiffness of the structure at the lowest possible weight. In a typical thin-wall structure, due to the small thickness of the skin, it is the covering that buckles, while the frame elements do not lose stability. Therefore, when testing thin-wall structures, it is extremely important to properly prepare the model so that the loss of stability is only local. The choice of stiffness of individual elements and the adopted technological process, which directly determines the properties of the system, are of fundamental importance. The text presents an exemplary solution of this problem, concerning the concept of research model with the given technological process. The model underwent the loading condition, which corresponds to the real conditions occurring during the flight. In the next stage, the characteristic properties of the composite thin-wall structure, which is a representative part of the aircraft, were recorded. The obtained results make it possible to determine the influence of the adopted solution on the character of the skin deformation and provide a basis for modifications and comparative analyses.